VCVERSE - A Video Conferencing Website with Controls - Smitha, D Souza; Ushasree, R; C., Fong Kim (INTI International University, 2024)
In today’s digital age, remote communication and collaboration are becoming increasingly important. Video Conferencing platforms have gained popularity as they provide an immersive and interactive way to connect with others. This paper aims to develop a video chat website with a built- in notes controller, using Nodejs and Python. One of the special features of the video chat website is the integrated note taking feature. Users can download the files during a video call to improve collaboration and information sharing. These files are synchronized in real – time with all participants to ensure that everyone can refer to the important points discussed during the call. To enable real-time video communication, WebRTC (Web Real-Time Communication) technology is integrated into the website. WebRTC enables browser-based peer-to-peer video and audio communication without the need for additional plugins or software installations. The resulting video chat website with features will provide a user-friendly and collaborate platform for remote communication and teamwork. It can be used in various fields such as education, business meetings, and remote collaboration of distributed teams.